The University of the Witwatersrand History Workshop and radical South African historical scholarship in the 1970's and 1980's - Tatham, Gayle Kirsten (Department of Historical Studies, 2016)
The thesis examines the History Workshop at the University of the University of the Witwatersrand in the context of radical South African historical scholarship. Not only is the History Workshop shown to mirror developments in radical scholarship but it is seen to guide and stimulate particular directions of research. The history of the Workshop is traced and its academic as well as popularising activities are examined. The Marxist social history approach, which was encouraged by the Workshop, is considered with reference to the social and political environment in which it emerged, and the international and local historiographical context. The issues, themes and concepts reflective of that approach are unpacked and some thought is given to their impact on Marxist categories of analysis. The History Workshop is seen to reflect and to have some influence on the direction pursued in labour and urban as well as rural history. In labour history, it pursued concerns of the social history of labour. Labour history was to take two different paths in the 1980's due partially to the influence of the Workshop group. Urban history grew rapidly as a field in the 1980's. The triennial Workshops reflected that development while the Workshop group particularly encouraged social history concerns within that field. The development of Marxist social history is seen in the change from an economistic approach in some of the papers presented at the first History Workshops to a broader social history emphasis in many of the later papers. The themes and issues arising out of urban Marxist social history are considered, as is their impact on the understanding of South Africa's urban history in general. The Workshop reflected and encouraged social history themes in rural history studies, which was another expanding field of research in the 1980's. These themes incorporated Africanist insight as well as an emphasis on oral history and local history. The Marxist social history studies, which were presented at the triennial Workshops, produced new insights into the rural history of South Africa which challenged earlier theories. The History Workshop with its materialist social history approach acted as a forum and as such, a catalyst for a radical scholarship in South Africa. The triennial workshops reflected what was happening in the terrain of Marxist social history. These Workshops, which attracted a large gathering of local, as well as foreign academics, legitimised that research and gave the Marxist social history scholars a certain standing within the local academic community. Although the study of South Africa's past may have similar directions in the late 1970's and 1980's without the presence of the Workshop, that presence gave a coherence and an added impetus to those routes of Marxist social history.